Factorial validation of Warr's well-being measure: a sample study on police officers - Bogas, S. (2015)
The purpose of this study was to test the factorial validity of the job-related affective well-being scale—the IWP Multi-Affect Indicator. The sample was composed of 1466 police officers and collected through self-report questionnaires. With the objective of validating the factorial structure of the IWP Multi-Affect Indicator, several models were tested using confirmatory factor analysis. The results supported a four-factor structure: anxiety, comfort, depression and enthusiasm, as well as a five-factor structure including the same four factors plus a second-order factor called global affective well-being.